Collaborative Governance Dalam Pelestarian Tradisi “Meanyud-anyudan” Di Desa Peliatan, Kecamatan Ubud, Gianyar - Pratiwi, Ni Luh Putu Eka Sandi; Wirantari, I Dewa Ayu Putri; Prabawati, Ni Putu Anik (Socio-political Communication and Policy Review, 2025)
This study aims to examine the shift in cultural values and the decline in community participation in preserving a tradition in Peliatan Village, which is known as an artistic and cultural village in Ubud District, Gianyar. To ensure its preservation, Peliatan Village implements a Collaborative Governance approach involving the government, the community, and the private sector specifically, PT PLN UID Bali through CSR funding assistance. This research employs a descriptive qualitative method with a case study approach, utilizing interviews, observations, and documentation. The collaborative governance framework is assessed using eight key indicators: network structure, commitment to a common purpose, trust among participants, governance, access to authority, distributive accountability/responsib ility, information sharing, and access to resources. The findings indicate that the successful preservation of this tradition depends on the collaboration of various stakeholders, particularly through environmental programs, community awarenes, and infrastructure support. However, several challenges persist, such as limited access to the river and the temporary nature of private sector assistance.This study recommends the development of long-term strategies to ensure the sustainability and effectiveness of tradition preservation efforts. It is expected to contribute to the development of collaborative-based cultural preservation policies. Abstrak Penelitian ini bertujuan untuk melihat pergeseran nilai budaya dan menurunnya partisipasi masyarakat dalam melestarikan suatu tradisi di Desa Peliatan, dimana Desa Peliatan dikenal sebagai desa seni dan budaya di Kecamatan Ubud, Gianyar. Untuk menjaga kelestariannya, Desa Peliatan menerapkan pendekatan Collaborative Governance yang melibatkan pemerintah, masyarakat, dan sektor swasta yaitu PT. PLN UID Bali melalui bantuan dana CSR. Penelitian ini menggunakan metode kualitatif deskriptif dengan studi kasus melalui wawancara, observasi, dan dokumentasi. Indikator collaborative governance yang digunakan adalah 8 indikator yaitu network structure, commitment to a common purpose, trust among the participant, governance, acces to authority, distributive accountability/responbility, information sharing, dan access to resources. Hasil penelitian menunjukkan bahwa keberhasilan pelestarian tradisi ini bergantung pada kolaborasi berbagai pihak, terutama melalui program lingkungan, kesadaran masyarakat, dan dukungan infrastruktur. Namun, terdapat beberapa tantangan, seperti akses menuju sungai yang terbatas dan sifat bantuan swasta yang temporer. Rekomendasi dari penelitian ini adalah diperlukan strategi jangka panjang agar pelestarian tradisi ini berkelanjutan dan efektif. Penelitian ini diharapkan berkontribusi dalam pengembangan kebijakan pelestarian budaya berbasis kolaborasi. Kata Kunci: Collaborative Governance; Pelestarian Budaya; Meanyud-anyudan; Desa Peliatan; Partisipasi Masyarakat.